Electrospinning: Current Status and Future Trends - Mohammadzadehmoghadam, S.; Dong, Yu; Barbhuiya, S.; Guo, L.; Liu, D.; Umer, R.; Qi, X.; Tang, Y. (2016)
With the emerging nanotechnology, nanoscaled materials have drawn much attention to wide research communities for many years. Nanoscaled fibrous materials offer a multitude of fascinating features such as high surface area-to-volume ratio and tuneable porosity, making them attractive for widespread applications. Among different methods for nanofibre fabrication, electrospinning is a simple and versatile process for generating ultrathin fibres from a variety of polymeric materials or composites. This chapter gives a holistic review on current approaches and developments in electrospinning and its future trends in manufacturing advanced materials.